PERSPEKTIF KRIMINOLOGI: ANALISIS TERHADAP PENYEBAB PENINGKATAN TINDAK PIDANA OLEH WARGA NEGARA ASING DI INDONESIA - Aliffia Ramadita Marani; Sohirin; M. Alvi Syahrin (IAIN Ambon, 2025)
Globalization and technological advances have led to increased human mobility across national borders, resulting in a rise in the number of foreign nationals (WNA) in Indonesia. While this phenomenon has brought positive impacts, it has also been accompanied by an increase in the number of crimes committed by foreign nationals. This study aims to analyze the causal factors (etiology) behind this increase through various criminological perspectives. Using a descriptive qualitative research method and a literature review approach, this study identifies the dominant types of criminal activities, ranging from visa abuse, cybercrime, to drug trafficking. The analysis results indicate that the primary causes of criminal activities by foreign nationals are multifactorial, including economic and lifestyle pressures, opportunities (weak supervision and easy access to technology), and rationalization of actions supported by cultural deviance. In response, a social crime prevention approach that focuses on mitigating root causes and reducing opportunities is a relevant strategy to implement. This study concludes that a comprehensive understanding of criminal etiology is necessary to formulate more effective and adaptive prevention policies. Keywords: criminal etiology, criminal acts by foreign nationals, social crime prevention, immigration